Social Life Cycle Assessment for Additive Manufacturing: A Review - Lúcio, João Francisco Alexandre (2017)
The aim of this dissertation is to assist in the development of the project FIBR3D – Hybrid Processes based on Additive Manufacture of Thermoplastic Matrix Composites Reinforced with Fibers, by providing a base insight on the Social Life Cycle Assessment methodology (SLCA) and other related methodologies. The main objective of this dissertation is to present a literature review to identify the existing life cycle based methodologies, which will give a base knowledge on how they work and how they can be implemented within the project FIBR3D. This study will help in the development of a life cycle based parametric model that will be used to assess the Additive Manufacturing technology that is being developed within the project. The main objective of this work is to study the Social Life Cycle Assessment methodology (SLCA), although it is considered that first it is needed to understand how the environmental Life Cycle Assessment (LCA) and the Life Cycle Costing (LCC) methodologies work, because they retain some similarities with each other and can be connected to create the Life Cycle Sustainability Assessment methodology (LCSA). After the study of the other two methodologies, the Social Life Cycle Assessment is analyzed with more detail. These methodologies were studied by analyzing information from papers, book chapters and standards. The keywords that were used in the search of the selected documents were, for example, “Life Cycle Assessment”, “Life Cycle Costing” and “Social Life Cycle Assessment”. After analyzing the selected documents, the information was summarized in tables so it is possible to conclude what can help in the development of the project and what can still be studied in more depth. In this dissertation 17 papers about LCA and LCC and 13 papers about SLCA are analyzed. In addition to the papers, some standards were also studied, because they are considered essential in the study of these methodologies. From all the analyzed papers, only two tried to link the SLCA methodology with the additive manufacturing technology (AM), which was unexpected, but plausible because the AM is a technology still under development. With the analysis of the papers it is possible to perceive that there is a great need to develop studies that apply these methodologies to assess the AM technology and products/processes in the phase of development. Apparently, despite the scarcity of studies, it is already clear that the AM technology is considered to have an immense potential to revolutionize industries and to change some standards at the social and society level.